Web-based smart diet system / Chan Hung Yee - Chan , Hung Yee (2003)
We all realize how important "diet" can be to the daily lifestyle. Many genetics, environmental, behavioral and cultural factor can affect health. Food choices are among the most pleasurable and effective decision to improve health prospects. Most people especially working adults are lack of concern and initiative to seek for healthy balance diet and lifestyle due to hectic schedule and bad eating habits. This can increase major risk factors for chronic diseases such as cancer, diabetes and heart attack. What constitutes to a balance lifestyle is consuming healthful diet. Healthful diet Healthful diet contains the amount of essential nutrients and calories that is needed to prevent nutritional deficiencies. Healthful diet, which contain the right balance of carbohydrate, protein, fat, vitamins and minerals can help to reduce risk for chronic diseases and be a part of a full and productive lifestyle. Such diets are obtained from a variety of foods that are available, affordable and enjoyable. They are simple day-to-day decisions that may affect health and well-being. Therefore, an interactive smart diet system proposed in this project will definitely help user to practice a healthful living by suggest the best menu and physical activities, which is the closest to user's taste and personal health condition to ensure a new and better way of living.